DAMPAK KEMAMPUAN VERBAL TERHADAP KUALITAS EKSPRESI TULIS - Amitya Kumara (Faculty of Psychology, Universitas Gadjah Mada, 2001)
Verbal ability is the important things to support the quality of writing. The verbal competence is consisted; (a) the vocabulary competence, (b) verbal reasoning. The reasearch is aimed at finding out the quality of writing expression by considering influencing variable verbal competence. Subject of the study were pupils at fifth grade at Kodya Yogyakarta, Primary School. The result of correlation analysis and qualitative analysis indicated that there is positive and significant correlation between quality of verbal competence and the quality of writing. Keywords: Verbal ability, writing